2013
DOI: 10.1017/s1461145712000028
|View full text |Cite
|
Sign up to set email alerts
|

Widespread decreases in cortical muscarinic receptors in a subset of people with schizophrenia

Abstract: These studies were undertaken to investigate the selectivity of cortical muscarinic receptor radioligand binding in muscarinic M(1) and M(4) receptor knockout mice and to determine whether a marked decrease in [(3)H]pirenzepine binding in Brodmann's area (BA) 9 from a subset of people with schizophrenia was predictive of decreased muscarinic receptors in other central nervous system (CNS) regions. Our data show that, under the conditions used, [(3)H]pirenzepine binding was highly selective for the muscarinic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 49 publications
6
47
1
Order By: Relevance
“…The present findings are especially interesting in light of multiple previous studies that cholinergic signaling Role of M 1 PAM in PCP-treated mice A Ghoshal et al is disrupted in the PFC and other cortical and limbic forebrain regions of schizophrenia patients (Berman et al, 2007;Dean et al, 2002;Raedler et al, 2007;Scarr et al, 2009a;Zavitsanou et al, 2004). Of particular interest is the recent finding that a defined subset of schizophrenia patients display decreases in M 1 levels in PFC and other cortical and forebrain regions (Dean et al, 2002;Gibbons et al, 2013). Interestingly, studies using brain autopsies from a broad range of schizophrenia patients show reduced methylation of the promoter for the gene encoding the M 1 mAChR subtype that may contribute to the reduced M 1 expression in their brain .…”
Section: Role Of M 1 Pam In Pcp-treated Micesupporting
confidence: 53%
“…The present findings are especially interesting in light of multiple previous studies that cholinergic signaling Role of M 1 PAM in PCP-treated mice A Ghoshal et al is disrupted in the PFC and other cortical and limbic forebrain regions of schizophrenia patients (Berman et al, 2007;Dean et al, 2002;Raedler et al, 2007;Scarr et al, 2009a;Zavitsanou et al, 2004). Of particular interest is the recent finding that a defined subset of schizophrenia patients display decreases in M 1 levels in PFC and other cortical and forebrain regions (Dean et al, 2002;Gibbons et al, 2013). Interestingly, studies using brain autopsies from a broad range of schizophrenia patients show reduced methylation of the promoter for the gene encoding the M 1 mAChR subtype that may contribute to the reduced M 1 expression in their brain .…”
Section: Role Of M 1 Pam In Pcp-treated Micesupporting
confidence: 53%
“…Studies comparing M1 and M4 muscarinic receptor density across diagnosis groups identified reductions in patients with schizophrenia, but not in bipolar disorder or major depression (Gibbons et al, 2009; Zavitsanou et al, 2004). Antipsychotic medication use or dose does not appear related to decreased muscarinic receptor density (Crook et al, 2001, 2000, 1999; Dean et al, 2002; Deng and Huang, 2005; Gibbons et al, 2013, 2009; Zavitsanou et al, 2004). Given the already decreased central cholinergic activity through fewer muscarinic receptors in schizophrenia patients, even a small amount of anticholinergic load may cause a significant adverse impact on cognition due to M1 receptor saturation, which may in turn make them more vulnerable to cognitive impairing effects of anticholinergic medication burden compared to those with mood-related psychotic disorders or healthy controls who have greater M1 availability (Tani et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Numerous post-mortem studies measuring M1/M4 selective radio-ligand binding (i.e. [ 3 H]pirenzepine) (Crook et al, 2001, 2000, 1999; Dean et al, 2002, 1996; Deng and Huang, 2005; Gibbons et al, 2013; Zavitsanou et al, 2004), as well as the levels of protein and mRNA (Dean et al, 2002; Mancama et al, 2003), have observed a widespread reduction of muscarinic receptors, notably M1, in postmortem brain samples of schizophrenia patients. Additionally, in vivo analyses identified a 20–35% decrease of muscarinic receptor availability in multiple brain regions in unmedicated patients with schizophrenia compared to the healthy controls (Raedler et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, under the assay conditions we use, [ 3 H] pirenzepine predominately binds to the CHRM1 Gibbons et al, 2013). Importantly, clinical and preclinical studies suggest that cortical CHRM1 is important in cognitive functions (Anagnostaras et al, 2003;Nathan et al, 2012).…”
Section: Introductionmentioning
confidence: 98%